1988
DOI: 10.1021/ja00210a082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a silver(I) triflate sandwich complex of 1,2:5,6:9,10-tribenzocyclododeca-1,5,9-triene-3,7,11-triyne. The first example of a 12-membered macrocycle sandwich complex

Abstract: CF3SO3Ag reacts with the macrocyclic triyne ligand in THF in different ratios within several days to give the title complex (I) (yield 5‐10%) and polymerized THF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…1821 Herein, we used the pseudo‐gas‐phase conditions induced by the [Al(OR F ) 4 ] − anions to stabilize salts of the [Ag(η 2 ‐C 2 H 2 ) n ] + ( n =1, 3, 4) cations. The parent compounds of all homoleptic [M(C 2 H 2 ) x ] n complexes (M=any metal; n , x =any number) are to date unknown in condensed phases 22–26. The exceptional stability of the [Ag(C 2 H 2 )] model complex allowed us to analyze the fine structure of the charge‐density distribution inside the valence shell of the silver atom by high‐resolution X‐ray diffraction at 10 K. This topological analysis provides the first experimental insight into the microscopic nature of acetylene fixation at a metal center.…”
Section: Calculated Complexation Energies [Kj Mol−1] Of Ag+ With C2h2mentioning
confidence: 99%
“…1821 Herein, we used the pseudo‐gas‐phase conditions induced by the [Al(OR F ) 4 ] − anions to stabilize salts of the [Ag(η 2 ‐C 2 H 2 ) n ] + ( n =1, 3, 4) cations. The parent compounds of all homoleptic [M(C 2 H 2 ) x ] n complexes (M=any metal; n , x =any number) are to date unknown in condensed phases 22–26. The exceptional stability of the [Ag(C 2 H 2 )] model complex allowed us to analyze the fine structure of the charge‐density distribution inside the valence shell of the silver atom by high‐resolution X‐ray diffraction at 10 K. This topological analysis provides the first experimental insight into the microscopic nature of acetylene fixation at a metal center.…”
Section: Calculated Complexation Energies [Kj Mol−1] Of Ag+ With C2h2mentioning
confidence: 99%
“…The phenanthrene 1a used in this study was synthesized according to our previously reported method.I nitially,w ea ttempted to observe the carbophilic interaction of as ilver(I) cation with an ortho-phenylene ethynylenes caffold [51,52] in 1a.…”
mentioning
confidence: 99%
“…[23][24][25][26] [28] zu dem höhersymme-trischen globalen Minimum der optimierten D 3 -Struktur. [29] Die Präferenz der niedrigeren Symmetrie der beobachteten + -Salzen gesehen werden.…”
unclassified
“…C 2 H 2 ) n ] + -Ionen (n = 1, 3, 4) -die bisher in kondensierten Phasen [22] unbekannten Stammverbindungen aller homoleptischen [M(C 2 H 2 ) x ] n -Komplexe (M = beliebiges Metall, n, x, beliebige Zahl) -zu stabilisieren. [23][24][25][26] (2) in einer Acetylen-Atmosphäre [Gl. (1)].…”
unclassified